Le groupe de codéveloppement : un levier de réflexivité des enseignants en transition professionnelle ? - Joëlle Morrissette; Yasmine Charara (Université de Provence, 2015)
The changing contexts of our time affect all professions, and teaching is no exception : teachers have unstable working conditions, which often place them in periods of professional transition. We suggested to four teachers from a secondary school located on the Island of Montreal to participate to a professional co-development group (PCG), in order to support them in what they experience as a professional transition. In the PCG, the group's members shared their varied expertise and the group's discursive resources marked each teachers practice stories. From two such and contrasted stories, we look at how this device foster reflexivity and we try to identify pitfalls.